Studi Jenis Alat Penangkapan Ikan Tradisional di Sungai Batang Bungo Kabupaten Bungo Provinsi Jambi - Muhammad Natsir Kholis; Mohd. Yusuf Amrullah; Irwan Limbong (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Batang Bungo River is one of the main rivers in Bungo Regency and is open water with a length of ± 50 km. Information about the construction of types of fishing gear in the Bungo river is still very limited. The purpose of this study is to identify and classify the types of traditional fishing gear used by Batang Bungo River fishermen in Bungo Regency, Jambi Province. The method used is the survey method. The study was conducted in October-November 2018 in the Batang Bungo watershed, passing four sub-districts consisting of: Rantau Pandan, Muko-Muko Bathin Tujuh, Bathin Tiga Ulu and Bungo Dani. The results showed that there were five groups and seven types of fishing gear consisting of gill net (jaring), traps (bubu/luka, tekalak dan sukam), falling gears (jala tebar), hook and lines (pancing tajur), grappling and wounding (tembak).